STUDI VARIASI UKURAN SERBUK SARI KEMBANG SEPATU (HIBISCUS ROSA-SINENSIS L.) DENGAN WARNA BUNGA BERBEDA - DENNI APRIANTY, NI MADE; KRISWIYANTI, ENIEK (2008)
Keywords: acetolysis; micrometri; axis polar; apperture; exine ornamentation

(untitled) (Jurnal Biologi Udayana, 2008)
The purpose of this study conducted to know variety of : long of axis polar, equatorial plane diameters, and P/E index of ten Kembang Sepatu (Hibiscus rosa-sinensis L.) with differnt colour flowers. Acetolysis method and 1 % Safranin staining used to make pollens slides, micrometri were used to measured long of polar axis and diameter of pollens. The result of this research showed : pollen structure have: 90,10 ± 3,02 ^im to 117,42 ± 1,37 l^m axis polar long, 89,66 ± 3,13 |^m to 112,92 ± 0,94 (xm equatorial plane diameter, and 0,99 to 1,04 P/E index. Based on these data is indicated that the type of the pollen are prolat sferoidal (except bud type red corolla, and white flower) polypantoporat type appertura and periporat ornamentation exine .